SYNTHESIS OF FLAVANONE-6-CARBOXYLIC ACID DERIVATIVES FROM SALICYLIC ACID DERIVATIVE - Muhammad Idham Darussalam Mardjan; Retno Ambarwati; Sabirin Matsjeh; Tutik Dwi Wahyuningsih; Winarto Haryadi (Indonesian Journal of Chemistry, 2012)
Synthesis of flavanone-6-carboxylic acid derivatives had been conducted via the route of chalcone. The synthesis was carried out from salicylic acid derivative, i.e. 4-hydroxybenzoic acid, via esterification, Fries rearrangement, Claisen-Schmidt condensation and 1,4-nucleophilic addition reactions. Structure elucidation of products was performed using FT-IR, 1H-NMR, GC-MS and UV-Vis spectrometers. Reaction of 4-hydroxybenzoic acid with methanol catalyzed with sulfuric acid produced methyl 4-hydroxybenzoate in 87% yield. The acid-catalyzed-acetylation of the product using acetic anhydride gave methyl 4-acetoxybenzoate in 75% yield. Furthermore, solvent-free Fries rearrangement of methyl 4-acetoxybenzoate in the presence of AlCl3 produced 3-acetyl-4-hydroxybenzoic acid as the acetophenone derivatives in 67% yield. Then, Claisen-Schmidt condensation of the acetophenone and benzaldehyde derivatives of p-anisaldehyde and veratraldehyde in basic condition gave 2'-hydroxychalcone-5'-carboxylic acid derivatives  in 81 and 71 % yield, respectively. Finally, the ring closure reaction of the chalcone yielded the corresponding flavanone-6-carboxylic acids in 67 and 59% yield, respectively.